Additionality of the Trans-European Transport Network (TEN-T): – Strategic Policy Implications related to Programme Renewal based on a Subjective, - Vestgaard, Jens (Proceedings from the Annual Transport Conference at Aalborg University, 1999)
The paper addresses the issues of European additionality within the Trans-European Transport Network (TEN-T) from a strategic perspective. The evaluation approach used is subjective and formative based on a comparative, dynamic analysis of programme objectives, performance and environmental requirements including accession of new member states. Increased EU investments in the TEN-T – in addition to the national investments - are only justified by the additionality provided by new infrastructure to the Community as a whole. In view of the forthcoming revision of the TEN-T Guidelines and the ongoing planning exercises for infrastructure development in the accession countries a new beginning – a new study seems to be necessary to identify new priority links which deliver tangible benefits and additionalities. The overall objective of the study should be to demonstrate how individual TEN-T projects contribute to a more efficient operation of a new network.